An integration of scientific and research and educational work in the process of future teachers’ university training as modern pedagogical problem (Pedagogy of Higher and Secondary Education, 2013)
Proshkin V. V. An integration of scientific and research and educational work in the process of future teachers’ university training as modern pedagogical problem.This article is about need to work out some special pedagogical system of university integration of science and education that defines strategic direction of science development of the university and discloses a technology of improvement future teachers’ professional training. The author analyzed the most significant literary sources and established that modern researches insufficiently solve problem of maximum association of science and educational process at all stages.
Keywords: integration of scientific and research and educational work; university training; future teachers